2016
DOI: 10.1007/s10646-016-1716-9
|View full text |Cite
|
Sign up to set email alerts
|

Spawning and multiple end points of the embryo-larval bioassay of the blue mussel Mytilus galloprovincialis (Lmk)

Abstract: Since the 1960s, little has been done to improve and simulate the use of short-duration chronic bioassays of bivalve embryos, particularly in mussels. However, these test organisms offer great advantages in relation to other groups, due to the ease of obtaining breeders in cultivation systems, in the environment and any time, and due to their high sensitivity to chemicals or contaminants. To contribute some methodological aspects, this study uses techniques to stimulate spawning or improve the obtaining of gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…During the fertilisation event, eggs are released as an intermittent pink cloud, while sperm is released in a thin, steady stream through the exhaling syphon cloud [ 69 ]. The KCl method from [ 70 ] was chosen as a spawning inductor, and carried out as follows: mussels were injected with 2 mL of 0.5 M KCl into the valve cavity and left for 2 h outside water. Then, they were randomly divided into 5 tanks for each treatment (n = 6 per replicate tank in a final volume of 2 L), considering that preliminary tests showed that mussels were more likely to spawn when placed with conspecifics and not in individual jars.…”
Section: Methodsmentioning
confidence: 99%
“…During the fertilisation event, eggs are released as an intermittent pink cloud, while sperm is released in a thin, steady stream through the exhaling syphon cloud [ 69 ]. The KCl method from [ 70 ] was chosen as a spawning inductor, and carried out as follows: mussels were injected with 2 mL of 0.5 M KCl into the valve cavity and left for 2 h outside water. Then, they were randomly divided into 5 tanks for each treatment (n = 6 per replicate tank in a final volume of 2 L), considering that preliminary tests showed that mussels were more likely to spawn when placed with conspecifics and not in individual jars.…”
Section: Methodsmentioning
confidence: 99%